PERALATAN HIDUP ORANG BADUY GOLOK MEMPERKUAT HUBUNGAN SPIRITUAL DAN BUDAYA LINGKUNGAN SEKITAR - Amriah; Encep Supriatna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Baduy Luar comunity, as part of Indonesi’ s indigenous communities, lives a simple life by utilizing traditional tools. These tools not only serve pracitial functions bat also embody a philosopy pf living in harmony with local wisdom and the environment. IN their daily lives, they use tools made from natural material,such as wooden sticks, canes, and earthenware. These tools reflect their abiliti to utilize nearby resources without damaging the environment. One of these tools is golok, amachete- like tool made of forged iron. It is approximately 30 cm long and 5 cm wide, with one side sharp and the other blunt. The handle is made of wood, and its sheath is carved from wood as well.The golok holds a significant role in their daily lives due to its multifuncionality. It is usude for chopping firewood, cleaning, and even processing food.Its versalility demonstrates The skills and efficiency in living a life fully dependent on nature. The use of traditional by integrating modern tecnology in a balanced way with their principles of life. This approach fosters harmonious interactions between humans and the environment, while also adapting to modern life.By learning about the traditional tool of the Baduy Luar community, we gain insight into how indigenous communities maintain self- sufficiency, simplicity, and respect for nature. This tipic is a crucial reflection inensuring traditional vaalues are preserved amidst the currents of modernization, particularly in sustainzation, particularly in sustainability and evironmental harmony.